2015
DOI: 10.1021/acsami.5b01732
|View full text |Cite
|
Sign up to set email alerts
|

Optical Pendulum Generator Based on Photomechanical Liquid-Crystalline Actuators

Abstract: For converting light energy into electricity, an optical pendulum generator was designed by combining photomechanical movement of liquid-crystalline actuator (LCA) with Faraday's law of electromagnetic induction. Bilayer cantilever actuators were first fabricated with LDPE and LCA. Their photomechanical movement drove the attached copper coils to cut magnetic line of force generating electricity. The output electricity was proportional to the changing rate of the magnetic flux, which was greatly influenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(89 citation statements)
references
References 28 publications
0
89
0
Order By: Relevance
“…The repeated exposure‐shield archives an oscillation motion of the bilayer film under light irradiation, which could be driven by visible light and UV light (Movie S2 and Movie S3 in the Supporting Information). The calculated light conversion efficiency from NIR irradiation was about 1.84 × 10 –4 %, which approaches that of the conversion efficiency of a photomechanical actuator of a liquid crystalline elastomer . In both cases, all energy driven the bending of the bilayer film comes from the light irradiation, but the light energy is transferred through the photo‐chemical mechanical transition in the liquid crystalline elastomer, while light energy is transferred via the photo‐thermal‐mechanical transition in the RGO/PDMS system.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The repeated exposure‐shield archives an oscillation motion of the bilayer film under light irradiation, which could be driven by visible light and UV light (Movie S2 and Movie S3 in the Supporting Information). The calculated light conversion efficiency from NIR irradiation was about 1.84 × 10 –4 %, which approaches that of the conversion efficiency of a photomechanical actuator of a liquid crystalline elastomer . In both cases, all energy driven the bending of the bilayer film comes from the light irradiation, but the light energy is transferred through the photo‐chemical mechanical transition in the liquid crystalline elastomer, while light energy is transferred via the photo‐thermal‐mechanical transition in the RGO/PDMS system.…”
Section: Resultsmentioning
confidence: 70%
“…The calculated light conversion efficiency from NIR irradiation was about 1.84 × 10 -4 %, which approaches that of the conversion efficiency of a photomechanical actuator of a liquid crystalline elastomer. [1] In both cases, all energy driven the bending of the bilayer film comes from the light irradiation, but the light energy is transferred through the photo-chemical mechanical transition in the liquid crystalline elastomer, while light energy is transferred via the photo-thermal-mechanical transition in the RGO/PDMS system. NIR light has a conversion efficiency about ten times higher than that of UV light irradiation, confirming that the RGO has advantages in the NIR response.…”
Section: Oscillation Of Rgo/pdms/rgo Sandwiched Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14,15 ] The remarkable and fast oscillation of LCN‐based oscillators makes them valuable in collecting solar energy and generating electricity. [ 16,17 ] Compared with the UV light or visible light, near‐infrared (NIR) light is more attractive and highly preferred due to its invisibility and biocompatibility for remote activation with highly spatial and time precision, exhibiting tremendous potential in practical application prospects such as the fabrication of biomedical devices and development of intelligent soft robotics. [ 18–22 ] Besides, based on the fact that the NIR light count more than 50% in solar spectrum, utilization of the NIR light also provides inspirations to achieve efficient exploitation of solar energy.…”
Section: Figurementioning
confidence: 99%
“…Using molecular motors, which are similar to bio-motors such as protein motors [4][5][6], has been a simple and promising strategy for developing these types of machines. In particular, azobenzene (Azo) derivatives [7][8][9][10][11][12][13][14][15][16][17][18][19] or other photo-responsive molecules [20][21][22][23] have been utilized as moieties that produce the driving force for photo-induced mechanical materials such as molecular motors. Several research groups have reported motive objects such as small particles [13][14][15][16]20] and liquid droplets [17,18] by using photo-responsive molecules that are sensitive to light stimuli.…”
mentioning
confidence: 99%